2001
DOI: 10.1089/15209150152811207
|View full text |Cite
|
Sign up to set email alerts
|

What We Can Really Expect from Telemedicine in Intensive Diabetes Treatment: Results from 3-Year Study on Type 1 Pregnant Diabetic Women

Abstract: Existing standards of the management of the diabetic patients are not efficient enough, and further improvement is needed. The major objective of this paper is to present and discuss the therapeutic effectiveness of an intensive care telematic system designed and applied for intensive treatment of pregnant type 1 diabetic women. The developed system operates automatically, every night transferring all the data recorded during the day in the patient's glucometer memory to a central clinical unit. In order to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 9 publications
1
50
0
1
Order By: Relevance
“…In two of three studies diabetic clinical outcomes improved with mhealth interventions. Wojcicki et al 35 found that patients who transferred daily glucose readings to physicians using a telematic system and received telephone medication regimen feedback had better diabetic glycemic control, as defined by mean blood glucose and glucose variability indices, than control subjects. Although there was no significant difference in number of hyperglycemic or hypoglycemic episodes in the control or intervention group, the absolute number of either event was lower in the intervention group.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In two of three studies diabetic clinical outcomes improved with mhealth interventions. Wojcicki et al 35 found that patients who transferred daily glucose readings to physicians using a telematic system and received telephone medication regimen feedback had better diabetic glycemic control, as defined by mean blood glucose and glucose variability indices, than control subjects. Although there was no significant difference in number of hyperglycemic or hypoglycemic episodes in the control or intervention group, the absolute number of either event was lower in the intervention group.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…66 Some studies examined remote monitoring of glucose meter data by a provider who then adjusted treatment in pregnant women with GDM or T1D. [69][70][71][72] We presented data at the American Diabetes Association (ADA) Scientific Sessions of interim analyses of a study using CGM alone or with ShareÔ remote monitoring technology in pregnant women with T1D. Share allows followers (family and friends) to view sensor glucose trends and receive alerts.…”
Section: Remote Monitoring In Pregnancymentioning
confidence: 99%
“…Systematic review and meta-analysis of the literature Two reviewers working independently considered six trials published in seven manuscripts (22)(23)(24)(25)(26)(27)(28) eligible for review, with perfect interobserver agreement (Table 2). One additional eligible study was presented as a poster at the 63rd Scientific Sessions of the American Diabetes Association in June 2003 (29).…”
Section: Secondary Outcomesmentioning
confidence: 99%